Total leucocyte count and platelet indices: novel, early diagnostic markers of acute appendicitis - Ravikkumar, Rithu; Vaidya, Kuladeep; Sharma, Aashish; Sukesh (International Journal of Research in Medical Sciences, 2023)
Background: Among the plethora of causes for patients presenting with an acute abdomen, appendicitis is the most common conclusive diagnosis. Known being controversial for its etiology and pathogenesis, diagnosis of acute appendicitis has been challenging despite the development of various clinical and laboratory studies. Inflammatory markers of hematological origin-total leucocyte count (TLC), platelet indices viz. mean platelet count (MPV), plateletcrit (PCT), and platelet distribution width (PDW), have long been preferred as rudimentary diagnostic parameters for acute appendicitis despite being contentious. Methods: An analytical and cross-sectional study among 100 individuals. Statistical evaluation of TLC, MPV, PCT and PDW of 21 appendicitis cases and 70 healthy individuals were complied. Results: Compared to the control group, cases showed significantly higher values of TLC and MPV while the PCT and PDW were normally distributed and showed no significant statistics. The sensitivity of TLC and MPV was determined to be 95.2%, 71.4%, and specificity 100%, 73.8% respectively. Conclusions: With equitable results, the routine and cost-effective TLC and MPV play a novel role in the early diagnosis of acute appendicitis.